Multisite phosphorylation drives phenotypic variation in (p)ppGpp synthetase-dependent antibiotic tolerance - Elizabeth A. Libby (Nature Portfolio, 2019)
Individual bacteria within isogenic populations can differ in antibiotic tolerance. Here, Libby et al. show that antibiotic tolerance variability can be driven by ‘noisy’ expression of a gene encoding a (p)ppGpp synthetase, which is in turn regulated by multisite phosphorylation of a transcription factor.